2015
DOI: 10.1016/j.jallcom.2015.05.173
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanisms of NaZn13-type phase in giant magnetocaloric La–Fe–Si compounds during rapid solidification and annealing

Abstract: a b s t r a c tThe promise of the LaeFeeSi alloys for energy efficient magnetic refrigeration devices stems from a strong magneto-structural transition in the La(Fe,Si) 13 (1:13) phase near room temperature. The formation of the 1:13 phase during rapid solidification was compared in detailed microstructural studies of the wheel-side and free-side surfaces of melt-spun ribbons. On the free-side, clusters of similarlyoriented crystallites are observed; chemical segregation of La, Fe, and Si leads to a nanoscale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…La-Fe-Si ribbons with a nominal composition of LaFe 11.5 Si 1.5 were fabricated by a melt-spinning technique. Details of the preparation have been reported elsewhere [20,21]. The resulting (as-spun) ribbons were sealed in evacuated quartz ampoules and subjected to isothermal heat treatment at 1273 K for 3 min or 2 h before rapid quenching to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…La-Fe-Si ribbons with a nominal composition of LaFe 11.5 Si 1.5 were fabricated by a melt-spinning technique. Details of the preparation have been reported elsewhere [20,21]. The resulting (as-spun) ribbons were sealed in evacuated quartz ampoules and subjected to isothermal heat treatment at 1273 K for 3 min or 2 h before rapid quenching to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic shape memory alloys [148,204] include Ni-Mn-In [167,175,192,261,283] doped with Co [136,172,241] and Si [122]; Ni-Mn-Sn [115,226]; NiMn-based B2 (Ni-Co)(Mn-Ti) [30], Ni-Co-Mn-Al films [189,190] [293], and metallic glasses [274]. Significant interest was devoted to the potentially viable LaFe 13−x Si x [137,200,284,288,290,292], doped with Co [249] and other additives [35], or partially hydrated [52][53][54][55]. For completeness, we mention Mn 3 CuN 1−x C x [147] and molecular magnets [128].…”
Section: ∆S T T C (K) ∆T S (K)mentioning
confidence: 99%
“…Previous research has reported that supercooling plays an important role in the nucleation competition between a-Fe and La(Fe,Si) 13 . [26] However, the transition area will be dismissed if the large volume fraction of the La(Fe,Si) 13 phase in directionally solidified LaFe 11.6 SI 1.4 alloys is brought about by the nucleation competition, which could imply a different valid mechanism.…”
Section: B Xrd Pattern Of Directionally Solidified Alloysmentioning
confidence: 99%